Validation of the movie for the assessment of social cognition in adolescents with ASD: fixation duration and pupil dilation as predictors of performance - Bast, Nico; Banaschewski, Tobias; Poustka, Luise (Journal of autism and developmental disorders, 2016)
Impaired social cognition is one of the core characteristics of autism spectrum disorders (ASD). Appropriate measures of social cognition for high-functioning adolescents with ASD are, however, lacking. The Movie for the Assessment of Social Cognition (MASC) uses dynamic social stimuli, ensuring ecological validity, and has proven to be a sensitive measure in adulthood. In the current study, 33 adolescents with ASD and 23 controls were administered the MASC, while concurrent eye tracking was used to relate gaze behavior to performance levels. The ASD group exhibited reduced MASC scores, with social cognition performance being explained by shorter fixation duration on eyes and decreased pupil dilation. These potential diagnostic markers are discussed as indicators of different processing of social information in ASD.